The Effect of Hypnotherapy on Serum Cortisol Levels in Post-Cesarean Patients - Rizkiani, Inne; Respati, Supriyadi Hari; Sulistyowati, Sri; Budihastuti, Uki Retno; Prasetya, Hanung (Journal of Maternal and Child Health, 2021)
Background: After cesarean section, there is often an increase in stress and anxiety which can have a negative effect on pain perception. Cortisol is the main stress hormone that regulates the duration and intensity of the stress response. Hypnotherapy is a therapy with a hypnotic method to reach someone's subconscious mind. Hypnotherapy is thought to be able to help patients in the post-section coping method because it can cause feelings of pleasure, satisfaction, safety, comfort and can make a person feel they have the strength of themselves to deal with the anxiety they experience. This study aims to analyze the effect of hypnotherapy on serum cortisol levels in postareaal section patients.Subjects and Method: This study was an experimental single-blind randomized controlled trial post-test group design which was conducted in the Obstetrics and Gynecology wards of Dr. Moewardi Hospital Surakarta and Dr. R Soetijono Blora Hospital. The subjects of the study were post-sectional patients who were hospitalized and met the inclusion and exclusion criteria. Subjects were divided into 2 groups, namely the hypnotherapy group which consisted of 15 post-sectional patients who received hypnotherapy and the control group which consisted of 15 postareaal patients who did not receive hypnotherapy. All subjects were examined for cortisol levels in the Prodia laboratory using the Chemiluminescent microparticle immunoassay (CMIA) method. The data of both groups were analyzed using the Mann-Whitney test.Results: The median, minimum, and maxi-mum cortisol levels in the hypnotherapy group were 3.60, 2.10, and 4.40 respectively, while the median, minimum and maximum cortisol values in the control group were 10.50, 8.20 and 32.80 respectively. Effect size= -2,2. The results of the analysis test showed a significant difference in mean values (p <0.001).Conclusion: Hypnotherapy has an effect on decreasing cortisol levels in post-cesarean section patients.Keywords: Hypnotherapy, Cortisol, Post-cesarean sectionCorrespondence: Inne Rizkiani. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Sura-karta, Jl. Kolonel Sutarto, Jebres, Surakarta, Central Java 57126.Journal of Maternal and Child Health (2021), 01(03): 258-266https://doi.org/10.26911/thejmch.2021.06.03.01